Rough Diamond : The Life of Colonel William Stephen Hamilton, Alexander Hamilton's Forgotten Son - Fielding, A. K. (Book collections on Project MUSE., 2021)
"Solider, politician, miner, pioneer, scion of the President, William Stephen Hamilton led a prolific life. Rough Diamond: The Life of Colonel William Stephen Hamilton examines the tumultuous early Republic period of American history through the life of Alexander Hamilton's son. Born in New York in 1797, the fifth son of President Alexander Hamilton, he was only six when his father was infamously killed in a duel with Vice President Aaron Burr. After resigning from West Point, Hamilton moved to frontier Illinois in 1817. The famous name of Hamilton that may have acquired him rank and prestige at one time was meaningless in a Midwestern frontier society driven by the Jacksonians. Yet, despite being hurled into a clash of economic, political, and cultural cultures, Hamilton determined to live his life by his own rules. A veteran of the Winnebago and Black Hawk Wars, Hamilton was elected to the Illinois House of Representatives before moving to the Wisconsin territory, where he founded the mining town of Hamilton's Diggings (Wiota, WI). When gold was discovered in California in 1848, he traveled west, where he would die in Sacramento in 1850. In Rough Diamond: The Life of Colonel William Stephen Hamilton, author A. K. Fielding expands the story of the Hamilton family. Hamilton's life offers a firsthand account of the formation of the Midwestern states, the realities of life on the frontier, and mass migration caused by the California Gold Rush"--